إشكالية قياس ظاهرة الفقر - بريكة, السعيد; عوام, نسرين (Université de M'sila, 2017)
This study aims to identify the phenomenon of poverty, as well as to highlight the most important methods of measuring it, the problems in this measurement, so there is a recognition by countries of different organizations to develop tools and indicators of measurement, which results closer to reality, among the most important findings of this study that Among the reasons for the lack of success in eradicating poverty is a discrepancy in the numbers and data resulting from the measurement, which makes it difficult to compare, as well as the lack of success of the combat policies. Therefore, it is necessary to take into account the definition or approach adopted for poverty, measurement index and verification of data collected for measurement .
Keywords: Poverty, the adopted approach to poverty, policies to combat poverty